The next generation of women leaders what you need to lead but won't learn in business school - Rezvani, Selena (Santa Barbara Praeger, 2010)
A groundbreaking, empowering collection of advice―richly illustrated with the stories of women at top echelons of their fields―that advances the leadership outlook for Generation X and Y women like no book before it.
Includes bibliographical references and index.
Keywords: Women executives